2012 19th International Packet Video Workshop (PV) 2012
DOI: 10.1109/pv.2012.6229729
|View full text |Cite
|
Sign up to set email alerts
|

Video quality evaluation in the cloud

Abstract: Abstract-Video quality evaluation with subjective testing is both time consuming and expensive. An interesting new approach to traditional testing is the so-called crowdsourcing, moving the testing effort into the internet. The QualityCrowd framework allows codec independent, crowd-based video quality assessment with a simple web interface, usable with common web browsers. However, due to its codec independent approach, the framework can pose high bandwidth requirements on the coordinating server. We therefore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…First studies by Keimel et al [140,141] have shown that crowdtesting can indeed provide results similar to the results from formal subjective testing in a laboratory environment. But as also discussed by Keimel et al [138], many challenges still remain before crowdtesting is a universally acceptable replacement for formal subjective testing.…”
Section: Roommentioning
confidence: 86%
“…First studies by Keimel et al [140,141] have shown that crowdtesting can indeed provide results similar to the results from formal subjective testing in a laboratory environment. But as also discussed by Keimel et al [138], many challenges still remain before crowdtesting is a universally acceptable replacement for formal subjective testing.…”
Section: Roommentioning
confidence: 86%
“…The same trend is emerging in the cloud services as well [11,12]. Therefore, in this section it is tried to present justifications on cloud-crowd computing by answering the following questions:…”
Section: Injecting Crowd Into Cloud Servicesmentioning
confidence: 99%
“…An example is the crowdsourcing system reported in [12] that considers a crowdsourcing system with the mission of video quality testing and then tries shifting the videos onto the cloud, thus optimizing the production of videos to the workers. Lenk et al based on such works, redesigned the cloud computing service stack and offered a new crowdsourcing layer on top of it entitled human as a service [46].…”
Section: Where To Inject Crowd?mentioning
confidence: 99%
See 2 more Smart Citations